A Phase I Clinical Trial of CD1c (BDCA-1)+ Dendritic Cells Pulsed With HLA-A*0201 Peptides for Immunotherapy of Metastatic Hormone Refractory Prostate Cancer. Issue 2 (February 2015) - Prue, Rebecca L.; Vari, Frank; Radford, Kristen J.; Tong, Hui; Hardy, Melinda Y.; D'Rozario, Rachael; Waterhouse, Nigel J.; Rossetti, Tony; Coleman, Robert; Tracey, Christopher; Goossen, Hans; Gounder, Vinay; et al.
Abstract : Preclinical studies have suggested that purified populations of CD1c (BDCA-1 + ) blood-derived dendritic cells (BDC) loaded with tumor-specific peptides may be a feasible option for prostate cancer immunotherapy. We performed an open-label dose-finding Phase I study to evaluate the safe use of CD1c + BDC in patients with advanced metastatic hormone refractory prostate cancer. HLA-A*0201-positive patients with advanced metastatic prostate cancer were recruited and consented. The vaccine was manufactured by pulsing autologous CD1c + BDC, prepared by magnetic bead immunoselection from apheresed peripheral blood mononuclear cells, with a cocktail of HLA-A*0201-restricted peptides (prostate-specific antigen, prostate acid phosphatase, prostate specific membrane antigen, and control influenza peptide) and keyhole limpet hemocyanin. The vaccine was administered intradermally or intravenously and peripheral blood was taken at predetermined intervals for clinical and immunologic monitoring. The vaccine was manufactured with a median purity of 82% CD1c + BDC and administered successfully to 12 patients. Each patient received between 1 and 5×10 6 fresh CD1c + BDC on day 0, followed by cryopreserved product in the same dose on days 28 and 56. The vaccine was well tolerated in all patients, with the most frequent adverse events being grade 1–2 fever, pain, or injection-site reactions. Vaccination with CD1c + BDC is therefore feasible, safe, and well tolerated in patients with advanced-stage metastatic prostate cancer.